The Effect Of Transactional Leadership And Work Skills On Employee Performance Mediated By Work Discipline At The Research And Development Agency Of Lahat Regency - Titi Hasanah; Isnurhadi Isnurhadi; Muhammad Ichsan Hadjri (UNIVED Press, 2024)
This study aims to determine the effect of transactional and work skills on employee performance mediated by work discipline at the Research and Development Agency of Lahat Regency. Respondents of this study were 60 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. Transactional leadership has a positive and significant effect on work discipline, 2. work skills have a positive and significant effect on work discipline, 3. work discipline has a positive and significant effect on employee performance, 4. transactional leadership has a positive and significant effect on employee performance, 5. work skills have a positive and significant effect on employee performance, 6. transactional leadership has a positive and significant effect on employee performance through work discipline, 7. Transactional leadership has a positive and significant effect on employee performance through work discipline, Transactional leadership has a positive and significant effect on employee performance through employee performance, and Work skill has a positive and significant effect on employee performance through employee performance through work discipline.